Dimensi Gerakan Dalam Proses Pembentukan Propinsi Banten - Yaya Mulyana (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2001)
Behind the legal-administrative procedures formally set out for creating a new province, a web of interaction among various parties in fact play a critical role in facilitating various segments of civil society to take part. It is through such a web of interaction that the formal procedures were pushed forward, to arrive at a succees in gaining official detachment of Banten from the province of West Java, The synergetic interlink between civil society and political society underlined the importance of treating them as medium for enganing in a political movement for achieving a particular goal.